An experimental investigation of colonel blotto games - Subhasish M. Chowdhury; Dan Kovenock; Roman M. Sheremeta (Center for Economic Studies and ifo Institute (CESifo), 2009)
This article examines behavior in the two-player, constant-sum Colonel Blotto game with asymmetric resources in which players maximize the expected number of battlefields won. The experimental results support all major theoretical predictions. In the auction treatment, where winning a battlefield is deterministic, disadvantaged players use a guerilla warfare strategy which stochastically allocates zero resources to a subset of battlefields. Advantaged players employ a stochastic complete coverage strategy, allocating random, but positive, resource levels across the battlefields. In the lottery treatment, where winning a battlefield is probabilistic, both players divide their resources equally across all battlefields.
Keywords: C72; C91; D72; D74; 330; Colonel Blotto; conflict resolution; contest theory; multi-dimensional resource allocation; rent-seeking; experiments; Nichtkooperatives Spiel; Konflikt; Potenzieller Wettbewerb; Allokation; Rent Seeking; Test